WiFi and WiMAX Secure Deployments - Trimintzios, Panagiotis; Georgiou, George (Journal of Computer Systems, Networks, and Communications, 2010)
Wireless Broadband offers incredibly fast, “always on” Internet similar to ADSL and sets the user free from the fixed access areas. In order to achieve these features standardisation was achieved for Wireless LAN (WLANs) and Wireless Metropolitan Area Networks (WMANs) with the advent of IEEE802.11 and IEEE802.16 family of standards, respectively. One serious concern in the rapidly developing wireless networking market has been the security of the deployments since the information is delivered freely in the air and therefore privacy and integrity of the transmitted information, along with the user-authentication procedures, become a very important issue. In this article, we present the security characteristics for the WiFi and the WiMAX networks. We thoroughly present the security mechanisms along with a threat analysis for both IEEE 802.11 and the 802.16 as well as their amendments. We summarise in a comparative manner the security characteristics and the possible residual threats for both standards. Finally focus on the necessary actions and configurations that are needed in order to deploy WiFi and WiMAX with increased levels of security and privacy.